2004
DOI: 10.1088/0031-9155/49/20/012
|View full text |Cite
|
Sign up to set email alerts
|

Extending the linear–quadratic model for large fraction doses pertinent to stereotactic radiotherapy

Abstract: Ongoing clinical trials designed to explore the use of extracranial stereotactic radiosurgery (ESR) for different tumour sites use large doses per fraction (15, 20, 30 Gy or even larger). The question of whether the linear-quadratic (LQ) model is appropriate to describe radiation response for such large fraction doses has been raised and has not been answered definitively. It has been proposed that mechanism-based models, such as the lethal-potentially lethal (LPL) model, could be more appropriate for such lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
240
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(249 citation statements)
references
References 18 publications
5
240
0
4
Order By: Relevance
“…While the LQ model is generally recognized as valid and forms the basis for much of the normal organ dose-toxicity thresholds that have been established, it is also generally recognized that high dose rates or fractions such as those present in high dose rate brachytherapy, hypofractionated therapy or stereotactic radiosurgery have cellular responses that can depart from the linear-quadratic model. Several supplementary or alternative models have been proposed to account for these high dose rates (37)(38)(39). To date none have commanded unequivocal consensus.…”
Section: Discussionmentioning
confidence: 99%
“…While the LQ model is generally recognized as valid and forms the basis for much of the normal organ dose-toxicity thresholds that have been established, it is also generally recognized that high dose rates or fractions such as those present in high dose rate brachytherapy, hypofractionated therapy or stereotactic radiosurgery have cellular responses that can depart from the linear-quadratic model. Several supplementary or alternative models have been proposed to account for these high dose rates (37)(38)(39). To date none have commanded unequivocal consensus.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the accuracy of the LQ model for survival rates at doses greater than 12 Gy has come into question,13, 14 due to clinical observations have found that the classical LQ model overestimated cell killing at high doses. For this reason, a modified linear quadratic model (MLQ), introduced by Guerrero and Li15 for describing large dose radioresponses, is used in this study to estimate survival fractions of cell lines after the IB‐IORT. The MLQ model can be expressed asSFfalse(xfalse)=exp(αDfalse(xfalse)βGfalse(italicλT+italicδD(x)false)D(x)2)Where the dose protraction factor δD(x) was included.…”
Section: Methodsmentioning
confidence: 99%
“…All the MLQ parameters for the five modeled cells are shown in Table 1. A value of 0.15 for δ and 0.693 for λ was chosen for all normal tissues and cancer cells 15, 17…”
Section: Methodsmentioning
confidence: 99%
“…Other analyses, however, suggest thatapplication of the model to larger fraction sizes could under predict the total dose required to produce a given effect. 16 , resulting in a less toxic but also less effective treatment. Other uncertainties cited above such as reoxygenation and redistribution are also particularly relevant as the total number of fractions in a treatment course diminishes.…”
Section: Hyupofractionation Has the Potential For Improving Therapeutmentioning
confidence: 99%